Serum Cystatin C Predicts Stroke Clinical Outcomes at 1 Year Independent of Renal Function - Ding, Yarong; Liu, Liping; Chen, Zimo; Li, Hao; Pan, Yuesong; Wang, Junfeng; Meng, Xia; Lin, Jinxi; Jing, Jing; Xie, Xuewei; Xiang, Xianglong; Wang, Yongjun (Frontiers in Neurology, 2021)
Objective: Serum cystatin C(CysC) is a sensitive marker of renal function to predict cardiovascular diseases. We aimed to investigate the predictive value of CysC for clinical outcomes independent of renal function in patients with acute ischemic stroke (AIS). Methods: We measured serum CysC levels in 10256 AIS patients from Third China National Stroke Registry (CNSR-III). The primary outcome was a combination of all-cause mortality and major disability (modified Rankin scale score, 3-6). Secondary outcomes included stroke recurrence and combined vascular events at one year. Outcomes were analyzed by using logistic regression and Cox proportional hazards models, respectively. Results: The median CysC of included patients was 0.95 mg/l (interquartile range, 0.83-1.10 mg/l). A U-shaped association was observed between CysC and primary outcome (all-cause mortality or major disability) (quartile [Q] 1 versus. Q2: adjusted odds ratio [aOR] 1.29, [95% CI 1.06-1.58], Pvalue=0.012; Q3 versus. Q2: aOR 1.12, [95% CI 0.93-1.35], Pvalue= 0.242; Q4 versus. Q2: aOR 1.35, [95% CI 1.10-1.65], Pvalue=0.004). Similar trend also existed in ‘preserved renal function’ patients. Adding CysC to a model containing conventional risk factors improved the model performance with integrated discrimination improvement (IDI) of 0.13% (Pvalue=0.016) and net reclassification index (NRI) of 13.10% (Pvalue<0.001) for primary outcome. No significant association was observed for stroke recurrence or combined vascular events rate in different CysC quartiles. Conclusions: CysC showed a U-shaped correlation with 1-year stroke clinical outcome, suggesting that serum CysC may not only be a simple candidate marker of renal function.